2018
DOI: 10.1523/jneurosci.2382-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Human Sensorimotor Cortex Control of Directly Measured Vocal Tract Movements during Vowel Production

Abstract: During speech production, we make vocal tract movements with remarkable precision and speed. Our understanding of how the human brain achieves such proficient control is limited, in part due to the challenge of simultaneously acquiring high-resolution neural recordings and detailed vocal tract measurements. To overcome this challenge, we combined ultrasound and video monitoring of the supralaryngeal articulators (lips, jaw, and tongue) with electrocorticographic recordings from the cortical surface of 4 subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 61 publications
5
45
1
Order By: Relevance
“…For the sensorimotor cortex, we found that 30% of recording sites revealed either lips-preferred or tongue-preferred activity, which had a topographic distribution: the electrodes located more dorsally on the sensorimotor cortex produced a greater high gamma power for the articulation of lips consonants while the electrodes that were located more ventrally yielded a greater high gamma power for tongue consonants. Thus, our results appear to recapitulate the expected dorsoventral layout for lips and tongue representations within the primary motor and sensory cortices (Penfield and Boldrey, 1937;Bouchard et al, 2013;Breshears et al, 2015;Chartier et al, 2018;Conant et al, 2018). We found that the density of articulator-discriminative observations closely aligned with the consonant onset in acoustic speech production.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…For the sensorimotor cortex, we found that 30% of recording sites revealed either lips-preferred or tongue-preferred activity, which had a topographic distribution: the electrodes located more dorsally on the sensorimotor cortex produced a greater high gamma power for the articulation of lips consonants while the electrodes that were located more ventrally yielded a greater high gamma power for tongue consonants. Thus, our results appear to recapitulate the expected dorsoventral layout for lips and tongue representations within the primary motor and sensory cortices (Penfield and Boldrey, 1937;Bouchard et al, 2013;Breshears et al, 2015;Chartier et al, 2018;Conant et al, 2018). We found that the density of articulator-discriminative observations closely aligned with the consonant onset in acoustic speech production.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast to the STN, the magnitude of cortical high gamma activity was not significantly different across recording locations. Given that the cortical recordings were confined to the orofacial segment of the sensorimotor cortex and the evidence of overlapping speech-related activation in the precentral and postcentral gyri (Cheung et al, 2016;Conant et al, 2018), this lack of spatial differentiation in the cortical high gamma activity is expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interpretation is supported by the specific functional involvement of the co-activated areas, which process visceral and somatosensory information underlying voluntary respiratory, laryngeal, and articulatory sensorimotor control (Banzett et al, 2000;Bouchard et al, 2013;Brown et al, 2008;Conant et al, 2014;Conant et al, 2018;Khalsa et al, 2009;Pfenning et al, 2014). Vocalization related movements are accompanied by proprioceptive, kinesthetic, and interoceptive consequences, which in turn are integrated with the motor system to guide song and speech production (Bernardi et al, 2015;Gozaine and Clark, 2005;Nasir and Ostry, 2006;Simonyan and Horwitz, 2011;Smotherman, 2007;Tremblay et al, 2003;Wyke, 1974).…”
Section: Insula Connectivity As a Function Of Accumulated Singing Tramentioning
confidence: 95%
“…Finally, our task of speech production was restricted to learning a spectrogram of the target signal. This simplified task did not account for the neural control of articulatory speech kinetics, likely involving the ventral sensory-motor cortex (54, 55).…”
Section: Discussionmentioning
confidence: 99%